Activation and deactivation of phosphorus in silicon-on-insulator substrates. (February 2016) - Chang, Ruey-Dar; Lin, Chih-Hung
Abstract: Phosphorus that had been implanted into silicon-on-insulator (SOI) substrates was activated using different annealing techniques to investigate phosphorus deactivation at low temperatures. A combination of amorphization and excimer laser annealing (ELA) greatly enhanced phosphorus activation. However, heavy doping with phosphorus reduced the thickness of the amorphous layer. Furnace annealing at 350 °C following ELA induced significant deactivation and the deactivation behavior was similar to that following rapid thermal annealing (RTA). The temperature-dependence of phosphorus deactivation in samples that were implanted with a dose of 5×10 16 cm −2 showed a transition at 400 °C. The deactivation behavior was more sensitive to temperature below 400 °C than above it. Samples with an implantation dose of 5×10 15 cm −2 exhibited only a weak temperature-dependence of deactivation at temperatures above 400 °C, implying that the transition of temperature-dependence is caused by the change of the deactivation mechanism with the phosphorus activation level.